Experiences of new graduate nurses working in a neonatal intensive care setting: a systematic review protocol of qualitative evidence. (October 2016) - Foster, Jann; Taylor, Christine; Patterson, Tiffany; Psaila, Kim
Abstract : Review question/objective: The overall objective of this systematic review is to identify, critically appraise and synthesize the experiences of new graduate nurses in the neonatal intensive care unit (NICU). The specific review question is: what are the experiences of new graduate nurses working in a NICU setting?